Audio fade-out profile shaping for interactive multimedia - Lupsa-Tataru, Lucian (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The present investigation refers an effective technique of shaping the audio fade-out profile in the current context of high demand for interactive multimedia. A rational function is employed in order to bring forth a highly versatile fade-out transition. To emphasize that the audio volume, i.e. the output of the selected rational function, is returned without noticeable delays during the fading process, a straightforward implementation in pure JavaScript is put forward in the paper, taking into account the most unfavorable case from the computational point of view.